Isolation and characterization of an aetiological agent in Whipple's disease. Issue 5983 (6th September 1975) - Clancy, R L; Tomkins, W A; Muckle, T J; Richardson, H; Rawls, W E
Abstract : A cell wall deficient form of an alpha-haemolytic streptococcus was grown from a prolonged monolayer cell culture of a lymph node taken from a patient with Whipple's disease. Serological cross reactivity was shown between the organism and the material within Whipple's disease macrophages positive for diastase-resistant periodic acid-Schiff (D./P.A.S.). In vitro studies characterized the organism as a facultative intracellular parasite which caused the accumulation within cells of D./P.A.S.-positive material. These results suggest that a pathogenic bacterium is the essential aetiological agent and that the culture of Whipple's disease tissues in hypertonic media may have practical value.